Grain size distribution for the sediment sample stations of the Ems river campaign 2016 - Pröfrock, Daniel; Zimmermann, Tristan; Irrgeher, Johanna; Pieper, Andrea; Erbslöh, Hans-Burkhard; Dutschke, Florian (In: Pröfrock, D et al. (2022): Freshwater and sediment data of the entire Ems river and its tributaries sampled during summer 2016 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.943673, 2022)
In order to understand and map the complex mass transport pathways and possible transformation processes of contaminants in coastal regions such as the German Bight, the main contributors must be identified and evaluated. In this context, rivers represent a major input source. In the framework of a river campaign from 20.06.16 till 25.06.2016, sediment and freshwater samples of the Ems and its tributaries were taken to determine their elemental and isotopic fingerprint and to investigate possible inputs into the German Bight. At every sampling station physicochemical parameters of the water column were measured directly after sampling with respective probes of a multimeter covering pH, dissolved oxygen, temperature and conductivity.